Digging for Literature on Tailoring Cultural Offers With and for Older People From Ethnic Minority Groups: A Scoping Review - Stephanie Tierney; Jordan Gorenberg; Marta Santillo; Debra Westlake; Geoffrey Wong; Kerryn Husk; Sofia Vougioukalou; Ruthanne Baxter; Shoba Dawson; Nia Roberts; Caroline Potter; Harriet Warburton; et al. (Lifestyle Medicine)
ABSTRACT Introduction Social prescribing addresses non‐medical issues (e.g., loneliness, financial worries, housing problems) affecting physical and/or mental health. It involves connecting people to external support or services, including ‘cultural offers’–events, groups and activities run within or by cultural organisations. Such offers need to be acceptable and accessible to diverse populations if forming part of a social prescription. Methods A scoping review was conducted to identify what existing literature, conducted in the United Kingdom, tells us about tailoring cultural offers for older people (aged 60+ years) from ethnic minority groups. Relevant literature was searched for on electronic databases, through Google, via a questionnaire to cultural organisations and by contacting the study's advisory group. Results Screening of 906 references–59 of which were read as full documents–resulted in six sources being included in the review. Some cultural activities described within them were run in traditional cultural spaces (e.g., museums, art galleries). Others were held in community centres. Data suggested that attending with others could reduce concerns about belonging. Barriers to engagement included low energy, language, poor confidence, accessing transport and unfamiliarity with a setting and/or activities. Provision of familiar food could help make people feel welcomed. Conclusions Reviewed papers showed that consulting with target groups is important to ensure that activities are inclusive and sympathetically delivered. The review also highlighted a paucity of published research on the topic; this means that cultural providers have little evidence to draw on when developing cultural offers for older people from ethnic minority groups.